Ethnic Differences in Physiological Responses to Fear Conditioned Stimuli - Martínez, Karen G. (PLoS One, 2014)
The idea that emotional expression varies with ethnicity is based largely on questionnaires and behavioral observations rather than physiological measures. We therefore compared the skin conductance responses (SCR) of Hispanic (Puerto Rican) and White non-Hispanic subjects in a fear conditioning and fear extinction task. Subjects were recruited from two sites: San Juan, Puerto Rico (PR), and Boston, Massachusetts (MA), using identical methods. A total of 78 healthy subjects (39 from PR, 39 from MA) were divided by sex and matched for age and educational level. Females from the two sites did not differ in their SCRs during any experimental phase of fear conditioning (habituation, conditioning, or extinction). In contrast, PR males responded significantly to the conditioned stimulus than MA males or PR females. Subtracting ethnic differences observed during the habituation phase (prior to conditioning) eliminated differences from subsequent phases, suggesting that PR males are elevated in their response to novelty rather than fear learning. Our findings suggest that, in addition to sex differences, there are ethnic differences in physiological responses to novel stimuli at least in males, which could be relevant for the assessment and treatment of anxiety disorders.